Analysis of air quality based on particulate matter (PM2.5 and PM10) by using two methods USEPA-AQI and IND-AQI and EF Factor in Ahwaz city in 2016 and 2017 - Fariba Hedayatzadeh; Alireza Ildoromi; Nasrin Hassanzadeh (Muhandisī-i Bihdāsht-i Muḥīṭ, 2020)
Background: The undesirable condition of air quality is one of the most important environmental problems that have challenged many of the world's cities. In this study, considering the importance of particle matter as one of the most important atmospheric pollutants in Ahwaz, the main objective is the air quality assessment of this city in terms of PM2.5 and PM10 in 2016-2017. Methods: The air pollution data were obtained from the Ahwaz Air Quality monitoring network. To check the status of suspended particles and determination of the contribution of each pollutant to air quality decline and also determine the responsible pollutant, USEPA-AQI and IND-AQI methods and Exceedance Factor were used. Results: The mean annual concentrations of PM10 and PM2.5 were 165.35 µg/m3 and 58.26 µg/m3, respectively. According to the results of the Ahwaz air quality index during this period, in terms of the PM10 pollutant concentration, 27 days and based on the concentration of PM2.5 pollutant in the total days, the condition were unhealthy. Comparison of seasonal concentrations of pollutants with NAAQS showed that the pollutants were higher than the NAAQS limit in all seasons. The air quality classification based on IND-AQI showed that the air quality level was poor in all seasons, and based on the USEPA-AQI, this condition of Ahwaz air has been created unhealthy air quality and Unhealthy for Sensitive Groups. Comparison of two methods showed that IND-AQI in the region was 273/90 and the responsible pollutant is PM10 but according to USEPA-AQI method, the responsible pollutant was PM2.5 with 136.93 AQI value. The EF factor also confirmed the results of the IND-AQI method and showed that the responsible pollutant in reducing air quality to poor and critical condition during these two years is PM10 contaminant. Conclusion: Therefore, based on the findings continuous monitoring of air quality, especially in terms of PM10 pollutant, is one of the main strategies for controlling air pollution in this city.